THE APPLICATION OF THE LEX SPECIALIS SYSTEMATIS PRINCIPLE IN THE ENFORCEMENT OF SPECIAL CRIMINAL LAW - Shilvi Grisminarti; Faizin Sulistio; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
This paper discusses the application of the lex specialis systematis principle in special criminal law as a solution to address overlapping regulations in its enforcement. This issue arises when law enforcers must choose the applicable legal provision in cases where a single criminal act is prohibited by multiple special criminal laws. In cases of pornographic content dissemination, challenges emerge due to overlapping regulations, including the Pornography Law, the Electronic Information and Transactions (ITE) Law, and the Sexual Violence Crime Law (TPKS). Each of these laws prohibits the dissemination of pornographic content (revenge porn) but assigns different legal subjects for criminal liability. This paper examines how law enforcers apply the lex specialis systematis principle as a guideline to determine the most appropriate legal provision, while also considering its implications for justice and legal certainty. This study underscores the importance of lex specialis systematis in ensuring clarity and effectiveness in handling complex criminal cases, particularly in pornographic content dissemination. Using a normative juridical method, this research analyzes existing legal norms through literature studies. It establishes parameters for law enforcers on how to apply the lex specialis systematis principle when multiple laws of equal standing regulate the same offense.